The Sundarbans : folk deities, monsters, and mortals - Sarkar, Sutapa Chatterjee (New Delhi : Social Science Press, 2010)
On the cultural history of Sundarbans, Bangladesh and India.
Includes bibliographical references and index.
Keywords: Sundarbans (Bangladesh and India) -- Civilization